Predictors of pelvic muscle exercise on the self‐efficacy of women giving birth. Issue 2 (16th April 2020) - Shin, Gisoo; Kim, Hye Jin; Kim, Miok
Abstract: This article is a reported of a study of the relationship between lower urinary tract symptoms and pelvic muscle exercise attitudes as well as effects on the self‐efficacy in childbirth women. Pregnancy and childbirth are normal physiological processes, but their effects on the genitourinary system are great. The enlarged uterus resulting from foetal growth is a major cause of urinary incontinence because it affects the tissues supporting the female pelvis and causes relaxation of the pelvic floor muscle and lower urinary function. A descriptive research study was performed from August to November 2017. Overall, 141 women after childbirth were conducted who living in South Korea. The outcome measure was the lower urinary tract symptoms, attitudes toward pelvic muscle exercise and self‐efficacy for pelvic muscle exercise. In this study, even though the women after childbirth had moderate level of lower urinary tract symptoms, their self‐efficacy for pelvic muscle exercise was low. Also, the gestational diabetes history and exercise duration after birth were identified as variables affecting self‐efficacy for pelvic muscle exercise. The present study showed that nurses should provide knowledge and strategies about pelvic muscle exercise to enhance self‐efficacy for post‐partum women.